Research on three-section type tool path planning algorithm for tooth hot pressing model cutting - Zhang, Lijun; Fang, Shaowei; Xu, Jiayi; Yang, Ning; Guo, Weijian; Wang, Hang; Li, Changliang (Computers & industrial engineering, 2022)
•A gingival line data optimization algorithm based on Bézier Curve is proposed.•A three-section type tool path planning method is proposed.•Experimental results show the burrs of machine-cut products are both less and small. In the process of automatic cutting of the tooth hot-pressed model, there are problems that the gingival line feature point data obtained by scanning is not suitable as a cutting route data and the tool path planning methods also lack universality. A trajectory conversion algorithm based on Bézier curve is proposed to process the feature points of gingival line by dividing the points to be optimized into four categories, which also uses the morphological characteristics of the gingival line to divide the hot-pressed model into three parts: anterior sides, posterior sides, left and right posterior sides. Each part adopts a different tool path planning method. The data analysis shows that if the density parameter ρ is 4, the number of optimized feature points can be increased by 3.5 times, and included angle of straight-line can be increased by about 16.5% on average. The path and posture of the tool changes continuously and smoothly, and the transition is natural at the junction. Cutting experiments further show that it takes 50 s for the machine to obtain an invisible orthotics. Regarding product quality as a criterion, the burrs of machine-cut products are both less and small. In a nutshell, the research effectively improves the stability of product quality and promotes production efficiency.